Strategi Internalisasi Nilai-Nilai Akhlak Dalam Pembelajaran Akidah Akhlak di MTs Midanutta’lim Mayangan Jogoroto Jombang - Nur Idayanti; Ahsanatul Khulailiyah (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2022)
Internalization strategy is a plan that contains a series of activities designed for the process of setting into the mind or personality, the actualization of values, standards, ideas, or practices from other people that determine the desired behavior for a system that educates by Islamic guidance towards the formation of a Muslim personality with noble character which includes in the learning process. Morals is a science that explains the meaning of good and bad explaining what humans should do. Moral values ??are an order of behavior that is embedded in one's soul. This study aims to: 1) To know the process of learning Akidah Akhlak in MTs Midanutta'lim Mayangan Jogoroto Jombang. 2) To know the process of internalizing moral values ??through learning Akhlak Akidah at MTs Midanutta'lim Mayangan Jogoroto Jombang. The method used in this study is a qualitative method with a qualitative descriptive design. Data collection techniques using interview techniques, and observation. From the results of research that has been conducted at MTs Midanutta'lim Mayangan Jogoroto Jombang, it can be concluded that the implementation of the strategy of internalizing moral values ??in schools is good but there are still several other inhibiting factors, namely there are still, some students who have not participated in all religious activities because of a lack of student awareness. In its application, the strategy of internalizing moral values ??can be applied in various forms, such as providing an understanding of morality in Akidah Akhlak learning and the teacher council has provided a pattern of coaching such as exemplary, habituation, and advice in the school, environment to shape students' morals for the better. The example of a good example and habituation in the daily life of the teacher will be a motivation for students to follow the habits that have been exemplified